Bank-firm relationships and the survival of non-financial firms during the financial crisis 2008-2009 - Kim Abildgren; Birgitte Vølund Buchholst; Jonas Staghøj (European Central Bank (ECB), 2013)
Utilising a unique data set with annual accounts from around 37,000 Danish non-financial firms spanning almost one and a half decade, we offer microeconometric evidence on bankfirm relationships and the survival of firms during the financial crisis 2008-9. Within the framework of accounting-based credit-scoring models we find that the probability of default during the crisis was significantly higher for firms with a “weak” bank than for comparable firms with a “sound” bank– even after controlling for differences in the credit quality of firms. We discuss how to interpret these results in relation to the real effects of financial crisis.
Keywords: E44; G21; G33; 330; bank-firm relationships; financial crisis; firm survival; probability of default